In silico studies, synthesis and antitubercular activity of some novel quinoline - azitidinone derivatives - Chitre, Trupti S.; Asgaonkar, Kalyani D.; Vikhe, Amrut B.; Patil, Shital M.; Garud, Dinesh R.; Khedkar, Vijay M.; Sarkar, Dhiman; Nawale, Laxman U.; Yeware, Amar (Current Computer-Aided Drug Design, 2021)
Background: Diarylquinolines like Bedaquiline have shown promising antitubercular activity by their action of Mycobacterial ATPase. Objective: The structural features necessary for a good antitubercular activity for a series of quinoline derivatives were explored through computational chemistry tools like QSAR and combinatorial library generation. In the current study, 3-Chloro-4-(2-mercaptoquinoline-3-yl)-1-substitutedphenylazitidin-2-one derivatives have been designed and synthesized based on molecular modeling studies as anti-tubercular agents. Methods: 2D and 3D QSAR analyses were used to designed compounds having a quinoline scaffold. The synthesized compounds were evaluated against active and dormant strains of Mycobacterium tuberculosis (MTB) H37 Ra and Mycobacterium bovis BCG. The compounds were also tested for cytotoxicity against MCF-7, A549 and Panc-1 cell lines using MTT assay. The binding affinity of designed compounds was gauged by molecular docking studies. Results: Statistically significant QSAR models generated by the SA-MLR method for 2D QSAR exhibited r(2) = 0.852, q(2) = 0.811, whereas 3D QSAR with SA-kNN showed q(2) = 0.77. The synthesized compounds exhibited MIC in the range of 1.38-14.59(mu g/ml). These compounds showed some crucial interaction with MTB ATPase. Conclusion: The present study has shown some promising results which can be further explored for lead generation.
Keywords: combilib; Molecular docking; mycobacterial ATPase; QSAR; Quinoline